Epidemiology of electrical and lightning related deaths and injuries among Canadian children and youth. Issue 2 (5th April 2004) - Nguyen, B H; MacKay, M; Bailey, B; Klassen, T P
Abstract : Among burn injuries, electrical injuries constitute a small but devastating fraction. To describe the epidemiology of electrical injuries in Canadian children, data on deaths and emergency department visits related to electrical injuries, including lightning strikes, were obtained from provincial coroners' offices and the Canadian Hospitals Injury Reporting and Prevention Program (CHIRPP) respectively, for the years 1991–96. Twenty one deaths and 606 emergency visits highlight that electrical related deaths, more frequent among school age children, are more likely the result of high voltage and lightning strike, while emergency department visits, more frequent among younger children, are more likely the result of low voltage. While the introduction of legislated standards for child safe outlets and educational programs for parents, children, and youth are recommended strategies toward reducing the frequency of these incidents, these strategies require further evaluation before their effectiveness can be estimated.